2001
DOI: 10.1152/jappl.2001.91.5.1999
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced oxidative stress affects erythrocytes in sedentary rats but not exercise-trained rats

Abstract: Oxidant stress is one of the factors proposed to be responsible for damaged erythrocytes observed during and after exercise. The impact of exertional oxidant stress after acute exhaustive treadmill running on erythrocyte damage was investigated in sedentary (Sed) and exercise-trained (ET) rats treated with or without antioxidant vitamins C and E. Exhaustive exercise led to statistically significant increments in the levels of thiobarbituric acid-reactive substance (TBARS) and H2O2-induced TBARS in Sed rats and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
70
2
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 21 publications
12
70
2
6
Order By: Relevance
“…Trained individuals tend to present low hemoglobin concentrations due to increase in the plasma volume. This sports anemia can also be observed in exercisedindividuals 19 . In the present study, increase in the hemoglobin content has been identified with performance of high intensity anaerobic exercise and with use of sports solution with maltodextrin.…”
Section: Discussionmentioning
confidence: 63%
“…Trained individuals tend to present low hemoglobin concentrations due to increase in the plasma volume. This sports anemia can also be observed in exercisedindividuals 19 . In the present study, increase in the hemoglobin content has been identified with performance of high intensity anaerobic exercise and with use of sports solution with maltodextrin.…”
Section: Discussionmentioning
confidence: 63%
“…The mixtures were incubated at 37°C in an incubator. Hemolysis was determined by measuring released Hb into the supernatant of the induced samples at 540 nm and expressed on the basis of the maximum absorbance [100 %] in the aliquots of erythrocytes completely hemolysed in distilled water [31].…”
Section: Hemolysismentioning
confidence: 99%
“…Dekkers et al 5) have reported an increase in ESR signals in the muscle tissue homogenate immediately after maximum exercise. Furthermore, many studies have shown an increase in thiobarbituric acid reactive substances (TBARS), which are an indicator of lipid peroxidation, in the blood and skeletal muscles 6) . Thus, it is thought that the volume of ROS generation generally increases depending on the intensity of exercise 7) .…”
Section: Generation Of Reactive Oxygen From Physical Exercisementioning
confidence: 99%